Fenomena Pembelajaran Bahasa Indonesia untuk ABK Tunarungu di SLB Aisyiyah Krian dan SLB Harmoni Gedangan, Surabaya - Putri, Sendy Kurnia; Sa’diyah, Jagad Nabilatu; Putri, Fender Maharani; Al Wahidah, Rahma Laili; Islamiyah, Masfufatul (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2023)
Deaf children are children with hearing loss which are classified into deaf and hard of hearing. The impact of deafness is the disruption of verbal/oral communication, both expressively (speaking) and receptively (understanding other people's speech), making it difficult to communicate with people in the environment. Learning Indonesian is one of the lessons that must be implemented in education in Indonesia. Indonesian is a science that has an important role in human life and for mastering science and technology. SLB Aisyiyah Krian uses an oral method where the teacher requires students to be trained in speaking orally assisted by sign language slowly from word to word to sentence. Harmoni Gedangan SLB uses role-play learning methods, one of which is language learning by prioritizing social interaction which aims to improve language skills for deaf children. This study uses qualitative research, namely about the characteristics of SLB Aisyiyah Krian and SLB in Sidoarjo District, namely Harmoni Gedangan SLB. For Aisyiyah Krian SLB, the authors made direct observations, while for Harmoni Gedangan SLB, the authors collected data from internet sources. The data collection technique at Aisyiyah Krian SLB is through direct observation by interviewing the principal and homeroom teacher for class VIII. The author asks several questions to the homeroom teacher of class VIII at Aisyiyah Krian SLB.